Navigating Community Dynamics: Management Strategies for Sustainable SME Development - Kamal, Titi (Golden Ratio of Community Services and Dedication, 2023)
This qualitative study explores community dynamics, management strategies, and sustainable development in the context of Small and Medium Enterprises (SMEs). Grounded in grounded theory and employing purposive and maximum variation sampling, data was collected through semi-structured interviews, focus group discussions, participant observation, and documentary analysis. Analysis involved iterative coding, axial coding, and theoretical sampling. Findings highlight the multifaceted nature of communities, shaped by intricate networks, cultural norms, and institutional frameworks. Management strategies such as stakeholder engagement, community-based initiatives, environmental sustainability, and digital innovation are crucial for SME success. Challenges include limited access to resources, regulatory constraints, and cultural barriers, while opportunities lie in leveraging diversity, fostering innovation, and contributing to community resilience. The study underscores the importance of holistic approaches, tailored interventions, and collaboration for sustainable SME development. It contributes theoretical insights into community dynamics and management strategies, offering practical implications for stakeholders. Further research directions include longitudinal studies, comparative analyses, and interdisciplinary approaches to deepen understanding and advance practice in navigating community dynamics for sustainable SME development.